Kindergarten Children’s Growth Trajectories in Reading and Mathematics: Who Falls Increasingly Behind? - Morgan, Paul L.; Farkas, George; Wu, Qiong (Journal of learning disabilities, 2011)
The authors used a large sample of children (N ≈ 7,400) participating in the Early Childhood Longitudinal Study–Kindergarten Cohort (ECLS-K) to estimate kindergarten children’s academic achievement growth trajectories in reading and mathematics. The authors were particularly interested in whether the growth trajectories of children with learning disabilities (LD) or speech language impairments (SLI)—as well as those of other groups of children—were consistent with a cumulative or compensatory developmental cycle. Both LD and SLI children displayed significantly lower levels of kindergarten reading achievement than nondisabled children. However, and over the subsequent 5 years of elementary school, only children with SLI lagged increasingly behind nondisabled peers in their reading skills growth. The authors observed a different pattern for mathematics achievement. Children with LD, but not SLI, lagged increasingly behind nondisabled children in their mathematics skills growth. The authors also observed some consistency in “poor-get-poorer” effects across reading and mathematic achievement for additional population subgroups. Those kindergarten children who were from lower socioeconomic status families, who were African American, and who more frequently displayed learning-related behavior problems initially had lower levels of reading and mathematics achievement and also lagged increasingly behind in their acquisition of these skills over time. Some groups of children, including those with SLI, experience a cumulative rather than a compensatory cycle of achievement growth.